The Breast Care Education and Breastfeeding Positions - Hunawa, Rachmawaty D; Siti Hajar Salawali; Dewi Suryaningsi Hiola; Sitti Fatimah Meylandri Arsad (Jurnal Pengabdian, 2025)
Lack of maternal knowledge about the importance of breast care during pregnancy affects the baby's milk production and exclusive breastfeeding behavior from birth to 6 months of age, Breast care is an important organ and therefore a matter that needs to be considered in preparation for the next breastfeeding., Knowledge of the correct breastfeeding techniques is necessary to breastfeed the baby while ensuring the proper bond and position of mother and baby for breastfeeding to be successful. The purpose of this study is to provide education on Breast Care and Breastfeeding Position for Pregnant and Lactating Women. The method of implementation in this activity is breast health care counseling and breastfeeding positions aimed at pregnant women and breastfeeding mothers in Hulawa village, Telaga district. The results obtained were that all participants experienced the same increase in score, which was 30 points, which reflected a positive change in their understanding of the material presented, Before the counseling, the participants' scores were in the range of 40 to 60, which reflected a low to moderate level of knowledge. However, after being given counseling, participants' scores increased to 70 to 90, indicating a better level of understanding. The percentage increase in scores varies between 50% to 75%, depending on each participant's initial score. The conclusion of Health counseling is an activity carried out to increase one's knowledge and abilities through learning practice techniques or instructions to change or influence one's behavior in achieving healthy living goals, Advice for pregnant and lactating women can practice breast care directly to help increase milk expenditure for baby nutrition and a good breastfeeding position can increase comfort for mothers and babies.